Tradurre l’immagine del mondo. L’approccio cognitivo alla traduzione sull’esempio del Cosmo (Kosmos) di Witold Gombrowicz - Paliczuk, Aleksandra (Neophilologica, 2013)
This paper is an attempt of a cognitive analysis performed on a piece of Polish literature translated into Italian, entitled Kosmos (Cosmos) by Witold Gombrowicz. The translation was made by Francesco M. Catalucci e Donatella Tozzetti. It presents the difficulties and traps that translators encounter in their work and emphasizes the complexity of translation process as a phenomena that is not only linguistic, but also operating on mental level of individuals as well as of linguistic communities. The analysis demonstrates some examples of Gombrowicz’s particular language and compares them with the translated expressions. It explains how important is for a succeeded translation not only the translator’s linguistic competence but, in particular, his wide knowledge about the nation that speaks the language of the text to be translated.